Фракціонування і властивості протеїназ клітин мишачої лімфоми NK/Ly - Луцик, М.; Навитка, С.; Придатко, О.; Стойка, Р. (Праці наукового товариства ім. Шевченка, 2010)
Виявлено, що лізат клітин мишачої лімфоми NK/Ly містить протеїнази, активність яких за рівнем гідролізу казеїну при рН 5,4 становить 26,3 мкг казеїну за хвилину на мг білка, а при рН 8,0 - 15,0 мкг казеїну за хвилину на мг білка. Для очистки
протеїназ і дослідження їх властивостей проведено фракціонування лізату клітин
NK/Ly за допомогою ступеневого висолювання амонію сульфатом, диференційного
осадження глобулінів за умов низької іонної сили і поступового зниження рН, хроматографії на колонці цібакрон-сефарози та афінної хроматографії на Т-гелі, а також шляхом імунопреципітації. Використання різних способів фракціонування дозволило досягти певного підвищення питомої протеолітичної активності препаратів, проте при цьому не вдалося одержати препарати протеїназ, які б були гомогенними за білковим складом. Результати електрофоретичного аналізу досліджуваних зразків протеїназ вказують на значну агрегацію білкових комплексів, до яких вони входять. Іншою особливістю протеїназ клітин лімфоми NK/Ly є нечутливість до
інгібувальної дії йодацетаміду, α-2 макроглобуліну і трасилолу. Обговорено роль різних типів протеїназ при пухлинному рості.
Ключові слова: пухлини, лімфома NK/Ly, протеїнази. Proteolytic activity, purification and properties of proteinases from murine lymphoma NK/Ly ascitic cells
were investigated. In cell lysates proteolytic activity as measured by hydrolysis of casein was on the level 26.3
ug of casein/min per mg of protein at pH 5,4 and 15.0 ug of casein /min per mg of protein at pH 8,0. By
fractional precipitation with ammonium sulfate proteins of lysates were separated into three fractions –
immunoglobulin-like, albumin and post-albumin. The highest specific proteolytic activity was detected in postalbumin
fraction, but the yield of protein material was the lowest. Disc electrophoresis of obtained fractions in
standard conditions at pH 8,9 revealed serum albumin as a predominant protein in albumin and post-albumin
fractions. In all fractions the substantial quantity of protein did not enter the gel and was retained in start
position, indicating on the presence of highly aggregated protein complexes. For elimination of blood plasma
proteins from post-albumin fraction immunoprecipitation with antibodies towards mouse blood proteins was
applied, providing three-fold increase in specific proteolytic activity. By chromatography on Cibacron blue
sepharose it was revealed that proteinases were not retained on the sorbent and passed through the column
resulting in three fold increase of proteolytic activity. Proteinases of immunoglobulin fraction were purified by
fractional precipitation of globulins by stepwise lowering of pH at low ionic strength. This approach was
however non effective as it did not provide an increase in proteolytic activity apparently due to damaging
effect on enzymes. Detectable proteolytic activity was revealed in subcellular particles obtained from ascitic
fluid by high speed centrifugation after elimination of cells. SDS PAGE revealed a numerous bands in each
fraction, derived mainly from material not entering the gel in non denaturating electrophoresis. This indicates
on association of proteinases with multimolecular complexes or subcellular particles. Purified proteinases
obtained from NK/Ly cells were insensitive to commonly used inhibitors trasylol, iodoacetamide and α-2
macroglobulin. The role of different types of proteinases in metastasis and other harmful effects during tumor
growth is discussed.
Key words: tumors, lymphoma NK/Ly, proteinases. Установлено, что в лизате клеток мышиной лимфомы NK/Ly содержатся протеиназы, активность
которых по уровню гидролиза казеина при рН 5,4 составляет 26,3 мкг казеина в минуту на мг белка, а
при рН 8,0 −15,0 мкг казеина в минуту на мг белка. Для очистки протеиназ и изучения их свойств проведено фракционирование белков лизата клеток NK/Ly с помощью ступенчатого высаливания сульфатом аммония, дифференцированного осаждения глобулинов в условиях низкой ионной силы и постепенного снижения рН, хроматографии на колонке с цибакрон-сефарозой и аффинной хроматографии на
Т-геле, а также с помощью иммунопреципитации. Применение различных методов фракционирования
позволило достичь определенного повышения удельной протеолитической активности препаратов,
однако не при этом удалось получить препараты протеиназ, которые были бы гомогенны по белковому
составу. Результаты электрофоретического анализа исследуемых образцов протеиназ указывают на значительную аггрегацию белковых комплексов, в которых они содержатся. Другой особенностью протеиназ клеток лимфомы NK/Ly является их нечувствительность к ингибиторному действию иодацетамида,
α2-макроглобулина и трасилола. Обсуждена роль различных типов протеиназ в процесах опухолевого
роста.
Ключевые слова: опухоли, лимфома NK/Ly, протеиназы.